Bromelain based enzymatic debridement in burn patients, its outcome, advantages and disadvantages - Shah, Kesha C.; Srivastava, Sunil N. (International Surgery Journal, 2024)
The aim of this study is to evaluate the outcomes, advantages, and disadvantages of bromelain-based enzymatic debridement in the management of burn wounds. Ours is a study in which we have selected 10 patients with deep dermal and full thickness burns admitted in SMS hospital, Jaipur. These patients underwent bromelain based enzymatic debridement applied as per the manufactures protocol. The patients were then observed for bromelain’s efficacy in debridement, wound healing, pain, duration of hospital stay, superadded bacteraemia and cosmetic outcome. Complete removal of burn eschar was observed in 9 out of 10 patients. Bromelain-based enzymatic debridement effectively removed necrotic tissue within a shorter timeframe compared to traditional methods. Patients treated with bromelain-based enzymatic debridement showed significantly faster wound healing, reduced infection rates, and lower pain levels during debridement. Improved cosmetic outcomes, such as reduced scarring and better skin texture, were also observed. Bromelain-based enzymatic debridement offers notable advantages in burn care, including expedited healing and enhanced patient comfort. Despite these benefits, the treatment's higher cost and the risk of allergic reactions are important considerations. The limited availability of bromelain-based products also poses a challenge. These factors suggest that while bromelain is a promising alternative, its use should be carefully evaluated based on individual patient needs and resource availability.